Venous thromboembolism in palliative care patients: what do we know?. Issue 191 (July 2020) - Noble, Simon
ABSTRACT: Despite a breadth of data on the management of cancer-associated thrombosis, all the studies informing clinical guidelines excluded patients receiving palliative care. Patients with advanced cancer have a higher rate of recurrent venous thromboembolism (VTE) and bleeding, making them one of the most challenging populations to treat. The dearth of population-specific research leaves clinicians with few options but to extrapolate data from clinical trials conducted on a healthier population. Recent observational studies have challenged the utility of doing this, suggesting the natural history of VTE in the advanced cancer patient may differ to our first beliefs and that a less aggressive approach to anticoagulation is warranted particularly near the end of life. This paper highlights what we know so far.